2022
DOI: 10.3389/fimmu.2022.1050211
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune response and the safety of third SARS-CoV-2 mRNA vaccine with longer interval after the second vaccination in kidney transplant recipients

Abstract: We evaluated the humoral and cellular immune responses and safety of the third severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccine with a longer interval after the second vaccination in kidney transplant recipients (KTRs). We enrolled 54 kidney transplant recipients without a history of coronavirus disease 2019 (COVID-19), who received a third dose of the vaccine. We assessed anti-SARS-CoV-2 spike antibody and antigen-specific T cells using enzyme-linked immunospot (ELISpot) against the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…These evidences supported the antibody responses in the longer interval group was better than those in the shorter interval group. The above data confirmed that an appropriate length of interval between COVID-19 vaccine doses should be part of an effective vaccination protocol (41). An optimal inoculation interval would reduce inoculation frequency and therefore limit costs, which is particularly important in the resource-poor areas with a shortage of vaccine supply.…”
Section: Discussionsupporting
confidence: 63%
“…These evidences supported the antibody responses in the longer interval group was better than those in the shorter interval group. The above data confirmed that an appropriate length of interval between COVID-19 vaccine doses should be part of an effective vaccination protocol (41). An optimal inoculation interval would reduce inoculation frequency and therefore limit costs, which is particularly important in the resource-poor areas with a shortage of vaccine supply.…”
Section: Discussionsupporting
confidence: 63%
“…The booster shot induced production of nAbs against the ancestral SARS-CoV-2 strain also in primary non-responder KTR subjects [ 13 , 14 , 15 ], although some of the recipients did not mount a detectable humoral immune response following the 3rd dose [ 16 ], while nAb titers were lower against Alpha, Beta, Delta and Omicron variants in both KTR and the general population [ 17 , 18 ], as confirmed by pseudotyped lentivirus [ 19 ] and live virus-based tests [ 20 ]. Moreover, the role of T cells in conferring protection has been underlined [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the cellular immune response in KTR assessing spike-specific IFN-γ production by ELISPOT assay [ 21 , 25 ] or ELISA quantization [ 26 , 27 ]. Here, we evaluated humoral and cellular immune responses in a small cohort of KTR and healthy individuals after the 2nd and 3rd dose of BNT162b2 Pfizer-BioNTech vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Manothummetha et al also indicated that Rmab use within 1 year was associated with a risk of decreased antibody acquisition rate [ 17 ]. Takai et al showed that the antibody acquisition rate is low within 2 years after Rmab administration in kidney transplant patients [ 18 ]; however, the longer-term effects of Rmab have not been investigated. It should be noted that B cells may be suppressed for nearly 5 years with adequate maintenance therapy, as revealed in this study.…”
Section: Discussionmentioning
confidence: 99%